2010
DOI: 10.1523/jneurosci.5530-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Shared Mechanisms for Opioid Tolerance and a Transition to Chronic Pain

Abstract: Clinical pain conditions may remain responsive to opiate analgesics for extended periods, but such persistent acute pain can undergo a transition to an opiate-resistant chronic pain state that becomes a much more serious clinical problem. To test the hypothesis that cellular mechanisms of chronic pain in the primary afferent also contribute to the development of opiate resistance, we used a recently developed model of the transition of from acute to chronic pain, hyperalgesic priming. Repeated intradermal admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 59 publications
3
70
0
1
Order By: Relevance
“…We also identified a role for PKA in medicating the pronociceptive effect of the stress on opioid modulation of DRG neuron excitability. Furthermore, we also found evidence that additional pathways were involved as the stress supernatant activated Gβγ-and PLC-dependent pathways that were not evident with the non-stressed supernatants; these opioid mediated pronociceptive signalling pathways have also been described in different animal model systems 31 41 47. Another indirect action of stress in the current study was the decrease in tissue endogenous opioids, presumably due to stress hormone-mediated suppression of opioid secretion by CD4+ T cells.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We also identified a role for PKA in medicating the pronociceptive effect of the stress on opioid modulation of DRG neuron excitability. Furthermore, we also found evidence that additional pathways were involved as the stress supernatant activated Gβγ-and PLC-dependent pathways that were not evident with the non-stressed supernatants; these opioid mediated pronociceptive signalling pathways have also been described in different animal model systems 31 41 47. Another indirect action of stress in the current study was the decrease in tissue endogenous opioids, presumably due to stress hormone-mediated suppression of opioid secretion by CD4+ T cells.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies31 have suggested that switching of opioid signalling to a pronociceptive action may be mediated by a switch in the G protein α subunits involved, from G i to G s , but might also involve translocation of βγ subunits and downstream phospholipase C (PLC) activation. Therefore, we studied the actions of a PLC inhibitor, U73122 (1 μM), and the βγ inhibitor, gallein (10 μM) (figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, morphine-induced Akt phosphorylation and Caspase-1 maturation in cultured neurons could be reproduced by DAMGO, which could also be inhibited by ATL treatment. In previous publications, peripheral DAMGO treatment-produced anti-nociception against PEG2-induced hyperalgesia declined dramatically after 3 days of twice daily treatment, which provided evidence that peripheral DAMGO administration could produce anti-nociception and tolerance-like behavior (Aley and Levine, 1997;Joseph et al, 2010). Although the correlation between DAMGO and NALP1 inflammasome activation was not investigated in this study, based on the present results, it's convincible that Caspase-1 activation and Akt phosphorylation after morphine incubation was highly associated with l-opioid receptor activation.…”
Section: The Spinal Inflammasome Mechanism In Morphine Tolerancementioning
confidence: 85%
“…Tolerance is defined as "the need for markedly increased amounts of substance to achieve intoxication or desired effect, and markedly diminished effect with continued use of the same amount of substance" [23]. It is due to desensitization and down-regulation of opioid receptors.…”
Section: Opioid-induced Hyperalgesia (Oih) and Tolerancementioning
confidence: 99%